Entanglements of Law and Space: An Introduction - Dudek, Michał; Eckhardt, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
Introduction to the thematic volume of Acta Universitatis Lodziensis. Folia Iuridica – devoted to the issue of law and space – provides basic context for the publication, placing special emphasis on the current state of legal geographical inquiries conducted by Polish scholars. Moreover, it briefly presents each article in the volume and comments on articles’ selected aspects to show how they can be located within the entire broad legal geography scholarship.